Pengaruh Kepuasan Transaksi Belanja Online Dan Kepercayaan Konsumen Terhadap Sikap Konsumen E-Commerce (Kasus Pada Pembelian Produk Shopee Di Kalangan Generasi Z Dusun Ciherang, Karawang - Abdullah Fatah; Citra Savitri; Syifa Pramudita Faddila (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The advancement of information and communication technology in the digital era has revolutionized societal consumption patterns, with online shopping platforms such as Shopee emerging as the preferred choice. This study examines the factors influencing consumer attitudes towards Shopee utilizing a quantitative approach and employing a multiple regression model. From a population of 143 Generation Z individuals in Ciherang village, Karawang, a sample of 105 participants was selected. The results underscore the pivotal role and mutual interaction of transaction satisfaction and consumer trust in shaping consumer attitudes towards the Shopee platform. The findings reaffirm the necessity of emphasizing consumer satisfaction and trust to bolster support for e-commerce, as well as the significance of integrated efforts to cultivate a robust relationship in the context of online shopping.